DNA promoter methylation and ERG regulate the expression of CD24 in prostate cancer - Tolkach, Iurii; Zarbl, Romina; Bauer, Simone; Ritter, Manuel; Ellinger, Jörg; Hauser, Stephan; Hüser, Laura; Klauck, Sabine; Altevogt, Peter; Sültmann, Holger; Dietrich, Dimo; Kristiansen, Glen (The American journal of pathology, 2021)
CD24 is overexpressed in many human cancers and is a driver of tumor progression. Herein, molecular mechanisms leading to up-regulation of CD24 in prostate cancer were studied. DNA methylation of the CD24 gene promoter at four loci using quantitative methylation-specific PCR was evaluated. Expression of CD24 in tumor tissues was studied by immunohistochemistry. To corroborate the results in vitro, ERG-inducible LNCaP TMPRSS2:ERG (T2E) cells and luciferase promoter assays were used. DNA methylation of the CD24 promoter was significantly higher in tumors than in benign tissue and was associated with biochemical recurrence-free survival, tumor grade, and stage. CD24 mRNA and protein expression were significantly higher in T2E-positive, ERG-overexpressing, and/or PTEN-deficient cases. Higher levels of CD24 protein expression conferred shorter biochemical recurrence-free survival, and these observations were confirmed using The Cancer Genome Atlas prostate adenocarcinoma data. In silico analysis of the CD24 promoter revealed an ERG binding site in between the DNA methylation sites. ERG overexpression led to a strong induction of CD24 mRNA and protein expression. Luciferase promoter assays using the wild-type and mutated ERG binding site within the CD24 promoter showed ERG-dependent activation. Collectively, our results suggest that promoter DNA methylation of the CD24 gene and T2E fusion status are factors involved in the up-regulation of CD24 in patients with prostate cancer.